Recreational activities and integral development in Latin American university students - Colque Ricce, Oscar Alfredo (2023)
This article analyzes recreational activities and integral development in university students in Latin America, considering the relevance this has for a holistic formation, where students make profitable use of their free time during their academic life. The methodology used was qualitative and made use of the documentary research design, carryingout a systematic review of different national and international bibliographic sources. The scientific articles reviewed were indexed in reliable databases, such as Web Of Science (ESCI), Scielo or Latindex. Among the main results, 96 % of Mexican university students had a predilection for the development of dance, theater and music workshops; more than 50 % of Ecuadorian university students said they agreed with the development of recreational activities; 67 % of Colombian university students said they were very satisfed with the recreational activities developed at the university; in Cuba, a recreational games program implemented at the university was effective and increased recreational sports activities by 64 %; while in Venezuela, 92 % of students did not know of the existence of such programs at their institution. Therefore, it is concluded that Latin American university students have a favorable predisposition towards the implementation of recreational activities programs in their study center, recognizing the  importance that this has for their integral development.